Dental management of patients with bilateral profound sensorineural hearing loss - César Tadeo Hernández Martínez; Norma Leticia Robles Bermeo; Carlo Eduardo Medina Solís; Sandra Isabel Jiménez Gayosso; Claudia Centeno Pedraza (Editorial Ciencias Médicas, 2017)
Introduction: hearing loss is reduced auditory acuity or a decrease in the ability to perceive sound. It may be sensorineural, conductive or mixed. Sensorineural hearing loss results from alterations in the inner ear, the auditory nerve or the auditory brainstem nuclei. Dental management of these patients requires willingness, knowledge and warmth on the part of the dental practitioner. Objective: report the dental management of a patient with bilateral profound sensorineural hearing loss. Case presentation: a female patient aged 7 years and 10 months diagnosed with bilateral profound sensorineural hearing loss attends consultation for dental pain. At physical inspection, it is observed that the patient is mesofacial with a convex profile. Intraoral examination found clinically healthy soft tissue, tooth alterations in number and position, moderate decay and poor hygiene. During clinical inspection, the patient was uncooperative (Frankl II). Treatment consisted in prevention, restoration, orthopedics and surgery. Management of the patient included use of basic sign language and a mask without the practitioner wearing a facemask, and modeling with other patients. The technique of say, show and do was replaced by show / smell, touch and do. Conclusions: pediatric dentists should have the skills required for the comprehensive care of patients with different capabilities. Behavior management and multidisciplinary care of very young patients is essential for a successful treatment. The clinical case herein presented highlights the effectiveness of modified behavior management, which increased the chances of success in the patient's dental rehabilitation and follow-up.